Progress and perspectives of fast ignition - Tanaka, K; Kodama, R; Kitagawa, Y; Kondo, K; Mima, K; Azechi, H; Chen, Z; Fujioka, S; Fujita, H; Johzaki, T; Lei, A; Matsuoka, T; et al. (2004)
Recent progress in the physics of fast ignition of fusion targets is reviewed here. Fundamental studies on hot electron energy transport show that the scheme looks promising if the heating pulse can be guided close enough to a compressed core. The idea of using cone-guided compression was first demonstrated experimentally under a Japan-UK collaboration. The use of the gold cone was extremely successful and showed a 103 neutron increase out of CD target implosion with a 300 J/0.5 ps enforced heating laser pulse. The heated temperature was close to 1 keV. In order to increase the temperature to 10keV, a 10kJPW-1 laser system is necessary. Osaka University has started constructing such a laser system.